2017
DOI: 10.1590/1981-863720170002000133222
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastic fibro-odontoma: case report

Abstract: RESUMOO fibro-odontoma ameloblástico é um tumor odontogênico misto benigno, assintomático e raro, que pode ser facilmente confundido radiograficamente e histopatologicamente com outras enfermidades. Normalmente atinge uma população entre a primeira e a segunda décadas de vida, sendo mais frequente em mandíbula e com predileção pelo sexo masculino. Este tumor caracteriza-se pela agenesia dentária no local do tumor, sem predileção por região anatômica, e por um aumento de volume intrabucal, podendo causar leve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…AFO is a benign mixed odontogenic tumor [76]. There is no sex predilection and this entity usually is seen in the first and second decades of life, which might also be a characteristic of the lesion [77].…”
Section: B-2-1) Pericoronalmentioning
confidence: 99%
“…AFO is a benign mixed odontogenic tumor [76]. There is no sex predilection and this entity usually is seen in the first and second decades of life, which might also be a characteristic of the lesion [77].…”
Section: B-2-1) Pericoronalmentioning
confidence: 99%
“…AFO is a benign mixed odontogenic tumor [76]. There is no sex predilection and this entity usually is seen in the first and second decades of life, which might also be a characteristic of the lesion [77].…”
Section: B-2-1) Pericoronalmentioning
confidence: 99%
“…There is no sex predilection and this entity usually is seen in the first and second decades of life, which might also be a characteristic of the lesion [77]. It is clinically represented as an asymptomatic swelling, delayed tooth eruption and displacement of adjacent teeth [76], [77]. They are more frequent in the posterior areas of the mandible and the involved tooth is often displaced in an apical position, which demonstrated that the origin of the lesion is above the tooth [17], [76].…”
Section: B-2-1) Pericoronalmentioning
confidence: 99%
See 2 more Smart Citations